KARAKTERISTIK HUJAN PENYEBAB BANJIR LAHAR DINGIN - , YOSUA ANDI ERLANGGA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Harm caused by the eruption of the volcano, which in this case is not only ended the Mount Merapi eruption at any time. However, after the alert status, there is still a danger that the cold lava flood. Conditions of the slopes of Mount Merapi are relatively \"bare\" trees as a result of the formation of hot clouds cause rain water that fell on the slopes can not be detained by tree roots growing. The subject matter of this research is to determine the depth of the peak rainfall occurring in or affecting the slopes of Mount Merapi cold lava flood events and know the characteristics of rainfall that cause cold lava flood. The study was conducted in Magelang regency, Central Java, with the object of study is the rain recording stations around the slopes of Mount Merapi, which is located in the Putih Watershed. Where's taken three (3) stations which is Argomulyo, Ngepos and Talun. The results showed that the depth of rainfall affects of cold lava flood. This is explained by the suitability of the time between the occurrence of flooding with rain events. Based on the results of data processing that occurs in the third rain rain stations, shows that rainfall variability is very high in the study area. However, of the three rainfall stations recording rainfall dominant cause of cold lava flood. This resulted in the analysis of rainfall characteristics should be investigated by the amount of rainfall is more than one station. The existence of precursor precipitation (antecedent rainfall) affects the flow of cold lava flood occurrence in the study area.